Comparison of Antimicrobial Activity ofAllium sativumCloves from China and Taşköprü, Turkey - Yetgin, Ali; Canlı, Kerem; Altuner, Ergin Murat (Wiley, 2018)
In this study, antimicrobial activities of two different samples ofAllium sativumL. from Turkey (TR) (Taşköprü, Kastamonu, Turkey) and China (CN) were determined. A broad spectrum of Gram-negative and Gram-positive bacteria (17 bacteria) including species ofBacillus,Enterobacter,Enterococcus,Escherichia,Klebsiella,Listeria,Pseudomonas,Salmonella, andStaphylococcuswere used for testing antibacterial activity. In addition, antifungal activity againstCandida albicanswas also investigated. Antimicrobial activity was tested by using 3 different processes (chopping, freezing, and slicing by the disk diffusion method). The results showed that TR garlic presented more antimicrobial activity than CN garlic. Mechanism of activity of CN garlic could be proposed to be different from that of TR garlic.
Keywords: Therapeutics. Pharmacology; RM1-950; Research Article; 3. Good health